2021
DOI: 10.21037/atm-20-6188
|View full text |Cite
|
Sign up to set email alerts
|

New horizons in non-small-cell lung cancer patients with ipsilateral pleural dissemination (M1a): review of the literature

Abstract: Non-small cell lung cancer (NSCLC) with ipsilateral pleural dissemination (pM1a) is generally contraindicated for surgery owing to the extremely poor survival. However, some studies have demonstrated that primary tumor resection (PTR) may prolong the survival of these patients. Besides, with the development of systemic therapy, it is still hard to decide the best therapy model for pM1a patients. Thus, we reviewed essential studies about NSCLC with pleural disease and summarized the progress of new techniques i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…It is now virtually universally accepted that there are subsets of patients with stage IV NSCLC who benefit from curative intent therapy, with surgery being done very selectively ( 5 , 25 ). Studies suggested that PTR was associated with improved survival in patients with NSCLC with pleural carcinomatosis or extrathoracic metastatic, particularly for those with single-organ metastasis ( 7 , 11 , 14 , 17 , 19 , 20 ). Further studies identified the specific group with <60 years old, female, adenocarcinoma, well differentiation, tumor site in lobe, T1-2, N0, and M1a that were potentially associated with more favorable survival ( 7 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is now virtually universally accepted that there are subsets of patients with stage IV NSCLC who benefit from curative intent therapy, with surgery being done very selectively ( 5 , 25 ). Studies suggested that PTR was associated with improved survival in patients with NSCLC with pleural carcinomatosis or extrathoracic metastatic, particularly for those with single-organ metastasis ( 7 , 11 , 14 , 17 , 19 , 20 ). Further studies identified the specific group with <60 years old, female, adenocarcinoma, well differentiation, tumor site in lobe, T1-2, N0, and M1a that were potentially associated with more favorable survival ( 7 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Not only distant metastatic lesions, but other factors such as concurrent intrathoracic metastatic lesion should also be considered. Recent studies show diverse clinical approaches in advanced NSCLC such as primary tumor resection, hyperthermic intrathoracic chemotherapy in patients with malignant pleural effusion, [50][51][52] and future studies that take various host and tumor-related factors into account are vital.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Additionally, several studies reported the effectiveness of hyperthermic intrathoracic chemotherapy (HITHOC) that it can control the symptoms and prolong the survival of patients with MPE. 34 Surgery combined with HITHOC has been recently reported to be an effective surgical intervention for selected pM1a patients to prolong life expectancy. A systematic review reported by Migliore et al 35 showed favorable outcomes for N0–1 NSCLC patients with MPE undergoing primary tumor resection plus HITHOC with a median survival time of 18 months and 2-year overall survival of 28.5%.…”
Section: Discussionmentioning
confidence: 99%